Management of imposter participants when conducting online research with victim-survivors and perpetrators of violence - Fiona C Giles; Mandy McKenzie; Minerva Kyei-Nimakoh; Lata Satyen; Laura Tarzia; Kelsey Hegarty (Methodological Innovations)
An increasingly common challenge facing researchers is participants falsifying their identity or their experiences to participate in online research. Imposter participants pose a threat to the integrity of research data, requiring careful risk mitigation strategies. In this case study report, we describe four projects across two institutions with victim-survivors and perpetrators of domestic, family and sexual violence in which we encountered imposter participants. We describe the technical, manual and ethical strategies we implemented to safeguard the integrity of our research. While necessary, these strategies were resource-intensive, and impacted participant recruitment and the wellbeing of researchers. We recommend a range of strategies at the study design, organisational and global level to better equip researchers with the tools to manage impost participants and maintain the integrity of data collected in research.